Protocolos de leitura: uma proposta didática para o trabalho com videoanimação - Costa, Márcia Carla Pereira (2022)
In contemporary society, reading becomes an increasingly complex action, which requires skills from the reader regarding the use of different semiotic resources (words, images, colors, lighting, sounds, etc.), their combinations to produce meaning effects. This research is guided by the following problem: What are the contributions of reading protocols for the referral of educational practices that effectively promote the formation of active responsive readers? It is assumed that reading is an interactive phenomenon of (re)constructing, negotiating and questioning possible meanings to texts and discourses from an active-critical/questioning responsive posture (ROJO, 2004; GOMES, 2017). This dissertation chooses as general objective to analyze the potentialities of reading protocols for working with video animations and as specific objectives: a) to present a theoretical compilation about reading conceptions; b) systematize the discussion made by Isabel Solé (1998) about reading strategies; c) discuss the reading protocols and their contributions to the formation of proficient readers; d) produce a suggested reading protocol for working with the video animation genre in the classroom. The methodological design of this research is organized from bibliographical research, constituted by three chapters: a) reading conceptions (KATO, 1994, 1995; CALIL, 1995; CORACINI, 2005); b) reading strategies (SOLÉ, 1998; GIROTTO; SOUZA, 2010) and c) reading protocols (SCHOLES, 1989; CHARTIER, 1996; LEAL, 2014; BORTONI-RICARDO, MACHADO, CASTANHEIRA, 2018; LEFFA, 1996; SANTOS, 2007). This research also presents a didactic proposal, which includes activities related to reading protocols aimed at teacher training. The video animation “Lost and Found”, by Andrew Goldsmith and Bradley Slabe (2018), was selected due to the modes of organization and the theme explored in the production in question. From the research carried out, it was possible to verify the relevance of working with reading protocols in multisemiotic texts, for the following reasons: a) studies on this issue are practically non-existent in the literature; b) the dissemination of information and communication technologies have expanded the social circulation of multisemiotic texts, which demands that teachers have training capable of meeting the demands of contemporary society; c) the constitutive complexity of multisemiotic texts, which present a combination of several resources, which requires skills to understand the choices made by the producers and to understand the effects of meanings; d) the relevance of methodological procedures that systematize the stages of the reading path, which allow the reader to analyze his own path, as well as the teacher to assess the students' reading proficiency and carry out more targeted interventions. Given the above, this research sought to build a reflection on the practice of reading articulated to the demands of the digital society.